Acute traumatic brain injury and the use of head computed tomography scans in the emergency department. (October 2022) - Rogan, Alice; Patel, Vimal; Birdling, Jane; Lockett, Jessica; Simmonds, Harnah; McQuade, David; Larsen, Peter
Introduction: The use of CT head scanning for traumatic brain injury (TBI) is a vital diagnostic tool, guided by risk stratification tools. This study aims to review the use of CT head scans and adherence to guidelines for TBI in two New Zealand emergency departments (EDs). Methods: Retrospective observational study of patients referred for head CT from EDs to exclude a significant intracranial injury between 1st September 2018 and 31st August 2019. Clinical data were collected regarding presenting patterns, identification of injuries on CT scan and adherence to National Institute of Clinical Excellence (NICE) CT head guidelines. Results: Out of 425 included cases, 41 (10%) patients had an intracranial injury seen on their CT head scan. Patients who reported loss (32% vs 20%, p < 0.05) or possible loss of consciousness (34% vs 22%, p < 0.05) and had a Glasgow Coma Score (GCS) <13 (17% vs 8%, p < 0.05) or focal neurology (10% vs 3%, p < 0.05) were more likely to have an intracranial injury on CT. Interestingly, 17 (41%) patients with CT diagnosed injuries had a GCS 15 and no focal neurology. NICE guidelines were adhered to in 364 (86%) of CT requests. In the 14% of cases that did not meet guideline criteria, all CT head scans were negative. Conclusion: CT head scans are a valuable tool in TBI, and guidelines successfully identify those with significant intracranial injuries. However, the rate of significant injury for the total population requiring head CT remains low, with over 90% of head CTs in the population normal, despite high guideline compliance, perhaps identifying a role for novel objective tests in ED guidelines internationally.